Al-Yamīnī : Fī akhbār dawlat al-malik Yamīn al-Dawla Abi ʼl-Qāsim Maḥmūd b. Nāṣir al-Dawla Abī Manṣūr Sabuktakīn - al-ʿUtbī, Muḥammad b. ʿAbd al-Jabbār (Miras Maktoob, ISBN: 9789004365452., 2020)
uḥammad b. ʿAbd al-Jabbār al-ʿUtbī (d. 428/1037 or 431/1040) was a native of Rayy who, through family connections, had entered the administration of the Sāmānids in Nishapur, attaining the rank of postmaster there. After several intermediary engagements he entered the service of the founder of the Ghaznavid dynasty Abū Manṣūr Sebüktigin (d. 387/997) and then, of his son Maḥmūd of Ghazna (d. 421/1030). From the time that al-ʿUtbī was sent as an envoy to Gharchistān in around 390/1000, there is a gap in his career until he offered his famous history of the Ghaznavids presented here to Maḥmūd-also called Yamīn al-Dawla-in around 410-11/1020. Since he was rewarded with a postmastership in the relatively insignificant town of Ganj Rustāq-which he soon lost to intrigue-he must have written this Arabic work mainly as a means to securing a job. Early dynastic history, ornate style, invaluable source of information on the early Ghaznavids.